Solanum pennellii backcross inbred lines (BILs) link small genomic bins with tomato traits. (18th July 2016) - Ofner, Itai; Lashbrooke, Justin; Pleban, Tzili; Aharoni, Asaph; Zamir, Dani
Summary: We present a resource for fine mapping of traits derived from the wild tomato species Solanum pennellii (LA0716). The population of backcross inbred lines (BILs) is composed of 446 lines derived after a few generations of backcrosses of the wild species with cultivated tomato (cultivar M82; LA3475), followed by more than seven generations of self‐pollination. The BILs were genotyped using the 10K SOL‐CAP single nucleotide polymorphism (SNP) ‐Chip, and 3700 polymorphic markers were used to map recombination break points relative to the physical map of Solanum lycopersicum . The BILs carry, on average, 2.7 introgressions per line, with a mean introgression length of 11.7 Mbp. Whereas the classic 76 introgression lines (ILs) partitioned the genome into 106 mapping bins, the BILs generated 633 bins, thereby enhancing the mapping resolution of traits derived from the wild species. We demonstrate the power of the BILs for rapid fine mapping of simple and complex traits derived from the wild tomato species. Significance statement: Wild species that are related to crop plants offer a means to understand the genetic basis of past domestication events and provide allelic diversity that can be used for future breeding of superior varieties. Here, we describe a high‐resolution resource for tomato, which can be used to rapidly link genomic regions to phenotypes.